Aspects of Bilingualism - Крапива, Юлія Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The paper in question presents the analysis of the bilingualism aspects. In the course of this study the main characteristics of the given phenomenon are considered taking into account the various forms of its existence, the ways and objective laws of the bilingualism development as well as its types. It is concluded that the given characteristics depend on the following parameters: the level of each language mastering, the language competence of the bilingual, the environment of the language acquisition, the degree of the languages autonomy, and the functions of each communication means.